Synthesis and Characterization of MgB2 Thin Films Prepared by 2.4 Mhz Ultrasonic Spray Pyrolysis System - Yakinci, Z. D.; Aydogdu, Y. (Springer, 2011)
Nano-sized B and Mg powders have been successfully deposited onto single crystal MgO(100) and Al2O3(001) substrates using 2.4 MHz ultrasonic spray pyrolysis system and an appropriate solution to obtain thin films of MgB2 superconductors. After an in-situ heating process, similar to 600-1000 nm thick superconductor films were obtained. The microstructure, electrical, and magnetic properties were characterized by means of particle size analyzer, XRD, SEM-EDX, R-T, and M-H analysis. The effect of particle concentration in the solution, spraying time, and heating temperature on the quality of the MgB2 films were discussed. The best T (c) and T (zero) results were obtained to be 39.5 and 37.4 K, respectively, for the film deposited on the Al2O3(001) substrates. Magnetic properties of the MgB2 films were investigated at 3 different temperatures and up to 5 T. Symmetric hysteresis loops for all temperature and field cases were obtained and maximum J(c)(mag) value was calculated to be 4.0x10(6) A cm(-2) at 10 K for 0 T for the film deposited on the Al2O3(001) substrates. The results obtained were found to be highly dependant on the particle concentration in the solution, heating temperature of substrates and carrier gas flow rate during spraying.
Keywords: MgB2 superconductor; Ultrasonic spray pyrolysis; MgB2 thin films; Superconducting MgB2 films